Analisis Determinan Kualitas Laporan Keuangan Lembaga Perkreditan Desa (LPD) di Kota Denpasar - Ni Putu Shinta Dewi; Ni Putu Lisa Ernawatiningsih (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2018)
The aim of the study was to obtain empirical evidence on the influence of the level of understanding of accounting, the function of the internal supervisory body, the quality of accounting information systems, the quality of human resources on the quality of village credit institutions (LPD) financial statements in Denpasar City. The data analysis technique used is multiple linear regression analysis. The results of the analysis show the level of understanding of accounting, the functions of the internal supervisory body, and the quality of human resources have a positive effect on the quality of LPD financial statements in Denpasar City. While the quality of accounting information systems does not affect the quality of LPD financial statements in Denpasar City.